VD_FINDINFO AM 67/09 - 4/2016 vom 9. Dezember 2015 - VD Tribunal cantonal (2015)
CHANGEMENT DE SEXE, TRAITEMENT À L'ÉTRANGER, LOI FÉDÉRALE SUR L'ASSURANCE-MALADIE | 24 LAMal, 32 al. 1 LAMal, 34 al. 2 LAMal, 35 al. 2 let. e LAMal, 36 al. 1 OAMal, 46 OAMal